Design and Simulation of Sandwich Structure of Exoskeleton Backplate Based on Biological Inspiration. Issue 5 (April 2021) - Peng, Xuefeng; Dai, Zongmiao; Liu, Jiasheng; Wang, Yongyuan
Abstract: The backplate is the main skeleton of the exoskeleton robot, and its structural strength and lightweight design are very important to the body structure of exoskeleton. In this paper, a design scheme of grille reinforced foam sandwich structure based on biological inspiration is presented. By analyzing the influence of core thickness on the mechanical properties of the sandwich structure, a new sandwich structure of exoskeleton backplate with a surface thickness of 2mm and a core thickness of 15mm was designed. Based on finite element software ABAQUS, the simulation calculation was carried out. The results show that the maximum stress of the sandwich structure is 298.5Mpa and the maximum strain value is 2730 με, which is less than the allowable value. This meets the structural strength design and lightweight design requirements.